An examination of county-level labor market responses to economic growth in Kansas - Schlosser, Janet A. (Kansas State University, 2008)
State and local economic development policies are often created with the goal of stimulating local economic activity through employment growth. The success of these policies is commonly measured by the number of jobs they create. Because labor markets are not bound by county lines, commuting and migration are important factors to consider when measuring employment growth in a region. This study used county-level data from the 2000 Census to predict labor force participation, unemployment, in-commuting, and out-commuting. The model was estimated using Ordinary Least Squares regression and was simulated to predict changes in labor force, unemployment and commuting as a result of a change in employment for all 105 Kansas counties. An increase in employment was found to increase the labor force participation, in-commuting, and unemployment, while decreasing the number of out-commuters. The increase in in-commuting causes many of the economic benefits expected to accrue to the county where the job growth occurred to be essentially exported to the county where the in-commuters live. Failure to account for the proportion of new jobs filled by in-commuters would lead to significant over estimations of local impacts of employment growth. These results suggest that regional coordination of economic development policies, through the use of tools such as tax-base sharing, would provide substantial gains to otherwise competing local governments.
Keywords: Commuting; Employment growth; Migration; Rural development; Community policy analysis; Local economic development; Economics, Labor (0510)